Barriers to physical activity participation in colorectal cancer survivors at high risk of cardiovascular disease. Issue 6 (18th August 2016) - Maxwell‐Smith, Chloe; Zeps, Nik; Hagger, Martin S.; Platell, Cameron; Hardcastle, Sarah J.
Abstract: Background: Lifestyle factors including inadequate physical activity may contribute to increased risk of developing cardiovascular disease in colorectal cancer survivors. Identification of the barriers to physical activity is important for forming an evidence base of factors to target in future physical activity programs aimed at improving cardiovascular health in this population. Methods: Colorectal cancer survivors ( N  = 24) from St. John of God Subiaco Hospital participated in semi‐structured interviews about their current physical activity behaviors and perceived barriers to physical activity. Results: Inductive thematic analysis of interviews revealed 5 overarching themes relating to barriers to physical activity: psychological barriers, environmental barriers, knowledge of guidelines, lack of practitioner support, and energy/age barriers. Conclusions: Novel findings revealed participants' dependence on practitioner support, including a reliance on practitioners to recommend lifestyle change. Survivors also revealed that regular checkups to monitor cardiovascular risk replaced the need for healthy lifestyle changes. Implications: With survivors holding the advice of clinicians in high regard, an opportunity exists for clinicians to facilitate lifestyle change. Health care professionals such as nurses can implement motivational strategies and provide additional health information during follow‐up visits, to ensure long‐term adherence. Individuals who reported psychological, motivational, and environmental barriers may benefit from interventions to improve self‐regulation, planning, and problem‐solving skills.